The changing perspectives of Tech Employees in Vietnam on the value of office during the New (Next) Normal. - Vu, Hang Thu (2025)
The thesis investigated the evolving perspectives of Vietnamese tech employees on the value of the office after the COVID-19 pandemic. The main goal was to understand how office design and work modes (onsite/hybrid) influenced collaboration, productivity, and employee satisfaction. A mixed-methods approach was employed, combining semi-structured interviews (N=15) and quantitative surveys (N=92) with tech professionals in Vietnam. Findings suggest that while open-plan offices facilitate communication, especially spontaneous ones, foster direct, faster problem-solving and team cohesion, they can hinder concentration because of noise and distraction. Drawbacks of open-plan offices regarding physical discomfort can have a negative link to the overall satisfaction of the office environment. Hence, despite working under different work modes, employees express a desire for more flexible, human-centric workspaces that balance openness with privacy for concentration and enhance well-being.